SUPPLY AND DEMAND: MARKET BALANCE - William, Clocksin; Gaibullayev, Sarvar; Qoldoshzoda, Basher (Science technology&Digital finance, 2023)
This article provides detailed information on supply and demand, market equilibrium. In addition to this, a brief overview of the supply and demand in the conditions of present-day Uzbekistan is given.